PENGARUH HALAL VALUE CHAIN DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA UMKM MAKANAN DAN MINUMAN : THE INFLUENCE OF HALAL VALUE CHAIN AND ENTREPRENEURIAL ORIENTATION ON THE PERFORMANCE OF FOOD AND BEVERAGE SMEs - Gusrian, Virgo; Nurmayanti, Poppy; Khoiriyah, Mayla (Universitas Riau, 2024)
The purpose of this study was to determine if the performance of food and beverage SMEs in Pekanbaru City is impacted by the halal value chain and entrepreneurial approach. The research method used was quantitative research, and primary data was utilized as the data source. The population of this study consisted of food and beverage SMEs operators in Pekanbaru City. Cluster sampling technique was employed for sample selection, with a total of 120 respondents participating in the study. Multiple linear regression analysis completed using SPSS Version 25 was utilized in the process of data analysis. There is a favorable and considerable effect that the halal value chain has on the performance of small and medium-sized enterprises (SMEs) in the food and beverage industry in Pekanbaru City, according to the findings of the study. This indicates that the better the implementation of halal value chain by SMEs operators, the higher the performance achievement of food and beverage SMEs in Pekanbaru City. However, entrepreneurial orientation variable does not affect the performance of food and beverage SMEs in Pekanbaru City. This suggests that the entrepreneurial orientation applied by SMEs operators does not have an impact and has yet to improve the performance of food and beverage SMEs in Pekanbaru City.